1987
DOI: 10.1021/jf00076a034
|View full text |Cite
|
Sign up to set email alerts
|

Hard-to-cook defect in black beans. Soaking and cooking processes

Abstract: Water absorption, solids loss, and electrolyte leakage were determined for soft and hard black beans during the soaking and cooking processes. All three parameters increased in hard beans during soaking. It is hypothesized that membrane damage or deterioration is responsible for these differences. During cooking, hard beans lost fewer solids and minerals and did not continue to hydrate to the same degree as the controls, probably as a result of restricted cell separation. Microscopic evidence indicated reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 6 publications
4
16
0
Order By: Relevance
“…The DA of the regions of interest (1450-1365 and 1180-1010 cm -1 ) indicated a significant separation between the soaking water of the control and the HTC red and black beans ( Figure 3B). These results are consistent with the work of Hincks et al (13) and Shomer et al (14) who found that solid loss and electrolyte leakage during soaking were greater for HTC beans than for control beans. These researchers also observed that HTC beans had higher water absorption.…”
Section: Resultssupporting
confidence: 93%
“…The DA of the regions of interest (1450-1365 and 1180-1010 cm -1 ) indicated a significant separation between the soaking water of the control and the HTC red and black beans ( Figure 3B). These results are consistent with the work of Hincks et al (13) and Shomer et al (14) who found that solid loss and electrolyte leakage during soaking were greater for HTC beans than for control beans. These researchers also observed that HTC beans had higher water absorption.…”
Section: Resultssupporting
confidence: 93%
“…The osmotic potential and matric potential contribute to the water potential of a system by the presence of dissolved solutes and hydrocolloids, respectively. Leached solids thus determine water uptake because of the decrease in the differential between intracellular and extra cellular water potentials [7].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic content of seed coats and cotyledons was reported to be changed during development for HTC defect (Jones and Boulter 1983). HTC grains cell wall reported to have smaller intercellular spaces (Gracia et al 1993) which attributed to the changes occurred in cell wall components during hardening (Hincks and Stanley 1987;Liu and Bourne 1995). This led to decrease in leaching of phenolic content during soaking among hard grains as compared to ETC grains (Xu and Chang 2008).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Limited inter as well as intra-cellular water availability is attributive of this defect (Hincks and Stanley 1987). b-eliminative degradation of pectin is also an important factor which resulted in the HTC defect.…”
Section: Introductionmentioning
confidence: 99%